PENERAPAN PSAK NO.30 TENTANG AKUNTANSI SEWA ASET TETAP PADA PT. RACHMAT KELANTAN SAKTI DI PALEMBANG - Rosita, Putri; Tjandrakirana DP, Rina; Meirawati, Eka (Universitas Muhammadiyah Palembang, 2018)
The activity of leasing fixed assets in a company has to follow standard regulation for each ofits lease transaction process. The accounting treatment for lease transaction should beapplied consistently according to SFAS No. 30 in order to compile financial statements.SFAS No. 30 about leasing has regulated lease acknowledgement, measurement, anddisclosure which in this case consists of leesee and leesor. The objective of this study is tofind out about accounting treatment for leasing fixed assets by PT. Rachmat Kelantan Saktiin Palembang during the period of 2015-2016 compared with SFAS No. 30. The methodused for this study is descriptive study. The result of this study shows that accountingtreatment for leasing fixed assets still uses lease operation method where at the end of leaseperiod, the fixed assets which have been leased will still belong to lessor, which in this is PT.Rachmat Kelantan Sakti in Palembang. Accounting treatment applied by PT. RachmatKelantan Sakti in Palembang hasn’t fully applied accounting treatment for leasing fixedassets according to SFAS No. 30.